Pengaruh Migrasi Masuk dan Upah Minimum Provinsi Terhadap Pengangguran di Kota Banda Aceh - Uswatul Hasanah; T. Zulham; Mahrizal Mahrizal; Affandi Affandi (JURNAL EKOMBIS, 2021)
This research was conducted in Banda Aceh with research variables consisting of in-house migration, provincial minimum wage and unemployment using secondary data based on the time of 2009-2018. This study used multiple regression analysis models, classic assumption tests, correlation coefficients (R), coefficient determination (R Adjusted), t test and F test. Based on this research obtained results that incoming migration has a positive and insignificant effect on unemployment with a sign value of 0.081 > 0.05 and the provincial minimum wage variable has a significant effect on unemployment with a significance of 0.010 < 0.05. The coefficient value of determination was 64 percent, so independent variables influenced as much as 64 percent and the remaining 36 percent were influenced by other variables outside the study. It is expected that the results of this research can be a consideration for the banda aceh government in implementing policies to overcome the number of unemployed as well as other policies on migration and the provincial minimum wage.Keywords: Incoming Migration, Provincial Minimum Wage and Unemployment